Antimicrobial efficacy of 0.05% cetylpyridinium chloride mouthrinses - SREENIVASAN, P. K; HARASZTHY, V. I; ZAMBON, J. J (Letters in applied microbiology, 2013)
This study evaluated the antimicrobial activity of two commercially available 0.05% cetylpyridinium chloride (CPC) mouthrinses with or without alcohol and examined its antimicrobial activity on oral bacterial species including fresh clinical isolates compared to a chlorhexidine mouthrinse and a control fluoride mouthrinse without CPC. Two different approaches were used to evaluate antimicrobial activity. First, the minimum inhibitory concentration (MIC) was determined for each mouthrinse against a panel of 25 micro-organisms including species associated with dental caries, gingivitis and periodontitis. Second, supragingival dental plaque obtained from 15 adults was incubated with the four mouthrinses to evaluate antimicrobial activity on micro-organisms in oral biofilms. Both CPC mouthrinses exhibited lower MIC's, that is, greater antimicrobial activity, against oral Gram-negative bacteria especially periodontal pathogens and species implicated in halitosis such as Aggregatibacter actinomycemcomitans,Campylobacter rectus,Eikenella corrodens,Porphyromonas gingivalis,Prevotella intermedia and Solobacterium moorei than the control mouthrinse. Ex-vivo tests on supragingival plaque micro-organisms demonstrated significantly greater antimicrobial activity by the CPC mouthrinses (>90% killing, P<0.001) and the chlorhexidine rinse (>98% killing, P<0.05) compared to the control fluoride mouthrinse. Whilst the chlorhexidine mouthrinse was most effective, mouthrinses containing 0.05% CPC formulated with or without alcohol demonstrated broad-spectrum antimicrobial activity against both laboratory strains and supragingival plaque bacteria compared to a control mouthrinse without CPC. These in vitro and ex-vivo studies provide a biological rationale for previous clinical studies demonstrating the efficacy of CPC mouthrinses in reducing supragingival plaque and plaque-associated gingivitis. Significance and Impact of Study: These in vitro and ex-vivo studies provide a biological rationale for previous clinical studies demonstrating the efficacy of CPC mouthrinses in reducing supragingival plaque and plaque-associated gingivitis.